2010
DOI: 10.1167/iovs.09-4724
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fibroblast Mechanostat Set Point and Mechanosensitivity: An Adaptive Response to Mechanical Stress in Floppy Eyelid Syndrome

Abstract: These changes may represent an adaptive response that allows tensional homeostasis to be maintained at the high levels of tissue stress experienced in FES. Gene expression studies point to a role for V-CAM1 and PPP1R3C in mediating changes in the dynamic range of mechanosensitivity of TFs. This work identifies FES as a useful model for the study of adaptive physiological responses to mechanical stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 54 publications
6
65
0
Order By: Relevance
“…The ability of GO fibroblasts to differentiate into adipocytes has been widely described [3], [5], [6], [10], [34], but little is known about their fibrotic potential. Using our well-characterised 3D model of collagen contraction, we have previously shown that fibroblasts derived from fibrotic ocular tissues display an increased contractile phenotype as compared to controls, and these fibroblasts retain, in vitro , both altered biomechanical properties and a specific molecular signature that might underlie their behaviour in disease [17]. Here we have uncovered a similar feature for orbital fibroblasts from patients with active Graves’ orbitopathy, suggesting that these cells have acquired an intrinsic fibro-proliferative phenotype and increased sensitivity to inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of GO fibroblasts to differentiate into adipocytes has been widely described [3], [5], [6], [10], [34], but little is known about their fibrotic potential. Using our well-characterised 3D model of collagen contraction, we have previously shown that fibroblasts derived from fibrotic ocular tissues display an increased contractile phenotype as compared to controls, and these fibroblasts retain, in vitro , both altered biomechanical properties and a specific molecular signature that might underlie their behaviour in disease [17]. Here we have uncovered a similar feature for orbital fibroblasts from patients with active Graves’ orbitopathy, suggesting that these cells have acquired an intrinsic fibro-proliferative phenotype and increased sensitivity to inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In a particularly important early study, uniaxial collagen gels fixed at both ends were observed to develop within a few hours an internal stress to a certain (apparently homeostatic) plateau level when seeded with fibroblasts. If this homeostatic state was perturbed by suddenly stretching or relaxing the gel, an immediate elastic change of stress in the gel was followed by a slow, exponential return back toward the homeostatic level [26, 27]. It is important to distinguish this behavior from passive viscoelastic stress relaxation common in many biological soft tissues [28].…”
Section: Experimental and Clinical Observationsmentioning
confidence: 99%
“…ECM adaptation is supported by a corresponding adaptational change in the contractile properties of tarsal plate fibroblasts 37 . Intrinsic cellular contractility is altered in FES allowing tarsal fibroblasts to maintain a dynamic range of contraction against a background of higher mechanical stress.…”
Section: Discussionmentioning
confidence: 99%
“…36 ECM adaptation is supported by a corresponding adaptational change in the contractile properties of tarsal plate fibroblasts. 37 Intrinsic cellular contractility is altered in FES allowing tarsal fibroblasts to maintain a dynamic range of contraction against a background of higher mechanical stress. The adaptation of the tarsal plate to pathological loading may therefore be taking place at multiple hierarchical levels including both cellular and ECM changes.…”
Section: Discussionmentioning
confidence: 99%